Education on the consequences of traumatic brain injury for children and adolescents with TBI and families/caregivers: a systematic scoping review. (2nd January 2023) - Pappadis, Monique R.; Lundine, Jennifer P.; Kajankova, Maria; Hreha, Kimberly P.; Doria, Nancy; Cai, Xinsheng Cindy; Flanagan, Joanne E.
ABSTRACT: Objective(s): To examine the breadth of education or training on the consequences of traumatic brain injury (TBI) for children and adolescents with TBI and their families/caregivers. Methods: Systematic scoping review of literature published through July 2018 using eight databases and education, training, instruction, and pediatric search terms. Only studies including pediatric participants (age <18) with TBI or their families/caregivers were included. Six independent reviewers worked in pairs to review abstracts and full-text articles independently, and abstracted data using a REDCap database. Results: Forty-two unique studies were included in the review. Based on TBI injury severity, 24 studies included persons with mild TBI (mTBI) and 18 studies focused on moderate/severe TBI. Six studies targeted the education or training provided to children or adolescents with TBI. TBI education was provided primarily in the emergency department or outpatient/community setting. Most studies described TBI education as the main topic of the study or intervention. Educational topics varied, such as managing TBI-related symptoms and behaviors, when to seek care, family issues, and returning to work, school, or play. Conclusions: The results of this scoping review may guide future research and intervention development to promote the recovery of children and adolescents with TBI.